Levels of Trace and Essential Elements in Sera of Chronic Renal FAilure Patients Before and After Dialysis - Jawad, A. H.; AL-Mulla, A.A.; Zardlekawee, A. .S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study included a group of (15) chronic renal failure patients (CRF), an addition group of (15) healthy individual  was concluded in this study for control. Trace and essential elements ( Zn, Cu , Ca , K , Na) were measured by atomic absorption and flam analyzer in sera of CRF patients pre and post dialysis and control groups. The results showed a significant ( p < 0.05) increase in Zn and k+ concentration in sera of CRF patients pre and post dialysis compared to the control group. While there is a significant decrease for copper concentration in sera of CRF patients pre and post dialysis compared to the control group.       There was no significant alteration (p> 0.05) in Ca and Na+ concentration in sera of CRF pre and post dialysis compared to the control group.